Long-term organ damage accrual and safety in patients with SLE treated with belimumab plus standard of care. (June 2016) - Bruce, I N; Urowitz, M; van Vollenhoven, R; Aranow, C; Fettiplace, J; Oldham, M; Wilson, B; Molta, C; Roth, D; Gordon, D
Objective: To examine long-term organ damage and safety following treatment with belimumab plus standard of care (SoC) in patients with systemic lupus erythematosus (SLE). Methods: Pooled data were examined from two ongoing open-label studies that enrolled patients who completed BLISS-52 or BLISS-76. Patients received belimumab every four weeks plus SoC. SLICC Damage Index (SDI) values were assessed every 48 weeks (study years) following belimumab initiation (baseline). The primary endpoint was change in SDI from baseline at study years 5–6. Incidences of adverse events (AEs) were reported for the entire study period. Results: The modified intent-to-treat (MITT) population comprised 998 patients. At baseline, 940 (94.2%) were female, mean (SD) age was 38.7 (11.49) years, and disease duration was 6.7 (6.24) years. The mean (SD) SELENA-SLEDAI and SDI scores were 8.2 (4.18) and 0.7 (1.19), respectively; 411 (41.2%) patients had organ damage (SDI = 1: 235 (23.5%); SDI ≥ 2: 176 (17.6%)) prior to belimumab. A total of 427 (42.8%) patients withdrew overall; the most common reasons were patient request (16.8%) and AEs (8.5%). The mean (SD) change in SDI was +0.2 (0.48) at study years 5–6 ( n  = 403); 343 (85.1%) patients had no change from baseline in SDI score (SDI +1: 46 (11.4%), SDI +2: 13 (3.2%), SDI +3: 1 (0.2%)). Of patients without organ damage at baseline, 211/241 (87.6%) had no change in SDI and the mean change (SD) in SDI was +0.2 (0.44). Of patients with organ damage at baseline, 132/162 (81.5%) had no change in SDI and the mean (SD) change in SDI was +0.2 (0.53). The probability of not having a worsening in SDI score was 0.88 (95% CI: 0.85, 0.91) and 0.75 (0.67, 0.81) in those without and with baseline damage, respectively (post hoc analysis). Drug-related AEs were reported for 433 (43.4%) patients; infections/infestations (282, 28.3%) and gastrointestinal disorders (139, 13.9%) were the most common. Conclusion: Patients with SLE treated with long-term belimumab plus SoC had a low incidence of organ damage accrual and no unexpected AEs. High-risk patients with pre-existing organ damage also had low accrual, suggesting a favorable effect on future damage development.